PERAN SOSIAL MEDIA INSTAGRAM SEBAGAI MEDIA KOMUNIKASI BISNIS DALAM PENINGKATAN PENJUALAN UMKM VOI CHURROS DI KOTA PEMATANGSIANTAR - Fidia Chairany Sitorus; Elsa Dameria Naibaho; Muzfirah Filzah; Fahri Irfarizki Siregar; Dian G Purba Tambak (MANAJEMEN, 2024)
This study aims to analyze the role of Instagram as a business communication medium in increasing the sales of VOI Churros, an MSME in Pematangsiantar City. The findings reveal that VOI Churros effectively utilizes Instagram features such as feeds, Reels, Stories, Highlights, collaborations with micro-influencers, and Instagram Insights. These strategies enhance brand visibility, expand audience reach, and foster strong customer interactions. Engaging visual content and creative promotions successfully attract consumer interest, while analytical tools optimize marketing campaigns. The use of Instagram has proven to positively impact sales, with up to a 20% increase in certain promotional campaigns. Moreover, seamless communication with customers through this platform builds loyalty and expands the market reach, even beyond Pematangsiantar. The effectiveness of this strategy is not solely determined by the platform itself but also supported by the quality of products and services provided. This study concludes that Instagram is an efficient marketing tool for VOI Churros to reach a wider market, improve customer engagement, and significantly drive sales growth. Consistent and well-planned strategies are crucial to maintaining this success in the future.